Perception and Exception of E-Banking Services of Commercial Banks in India - Devanadhen, Dr. K.; Sivakumar, Dr. V. (International Journal of Advanced Science and Technology, 2019)
Banks need to understand the attributes that customer use to judge service quality and enhance service quality. The paper tries to examines the customers’ perceptions and expectation towards internet banking service quality of banks in Villupuram district, Tamilnadu. Information quality (content), aesthetic design, ease of use, reliability, responsiveness, security and service variety dimensions were identified to measure the service quality of internet banking. The researcher determines 385 sample for the study by adopting Cochran (1977) formula. E-banking service quality scalewas refined and it turnup with six dimensions and 23 items, loss of 18 items and responsiveness dimension in purification of scale.The study performed the perception-expectation matrix to provide strengths and weaknesses of six dimensions of the e-service quality of the banks. The e-service quality are presented in two dimensional chart to provides the cues on the dimension of e-service quality, which enables the bank to improve or sustain the various service with limited time and resources. Security and service variety comes under low-priority improvement area. The dimension of aesthetic design, reliability and information quality comes under maintenance reinforcement area. Keywords: e-banking service, information quality, aesthetic design, ease of use, reliability, responsiveness, security, service variety